Compliance with reporting standards in Mobile App interventions for ART Adherence among PLHIV - Abdulhammed O. Babatunde; Dimeji A. Olawuyi; Folashade A. Olajuwon; Isaac O. Ekundayo; Olatokun S. Akano; Olutola V. Awosiku (AIDS Research and Therapy)
Abstract Introduction In recent decades, there has been a proliferation of mobile health (mHealth) interventions to address public health challenges such as HIV/AIDS. Hence, there is a need for standardizing the report of mHealth interventions and frameworks to enable effective knowledge sharing and promote developments. This study aims to review publications on mobile applications used for antiretroviral therapy (ART) adherence among people living with HIV (PLHIV) to evaluate their compliance with the standard reporting guideline by the WHO. Method A comprehensive search of published literature was conducted on PubMed, PubMed Central, and MEDLINE databases. We selected randomized controlled trials reporting mobile applications used to improve ART adherence among PLHIV. Only studies published in the last 10 years and the English language were included. Each selected study was reviewed by two independent reviewers against the standard 16-item checklist developed by the WHO. Results A total of 16 studies were included in the review. Most of the studies were conducted in the United States of America (n = 7). Only 4 (25%) of the studies reported more than 70% (11/16) of the items on the standard reporting checklist by WHO. More than 80% of the studies reported the intervention content (n = 15) and intervention delivery (n = 13). The least reported items were; interoperability/Health Information Systems (HIS) context (n = 2), infrastructure (population level such as electricity, internet connectivity, etc.) (n = 4), and cost assessment (n = 4). However, these are important factors that ensure the sustainability and usability of mHealth intervention, especially in low- and middle-income countries. Conclusion Most mHealth interventions promoting ART adherence did not comply with the standard reporting guideline. The lack of standardization of mHealth interventions may be responsible for increased siloed mobile applications. Hence, there is a need for global adoption of the checklist by Ministries of Health, international organizations, journals, and relevant authorities.